2020
DOI: 10.1016/j.enbuild.2020.110261
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive (non-contact) measurements of human thermal physiology signals and thermal comfort/discomfort poses -A review

Abstract: Non-invasive (non-contact) measurements of human thermal physiology signals and thermal comfort/discomfort poses-A review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(36 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…Factor analysis is a common analytical method to test the validity of the facet. rough exploratory factor analysis, on the one hand, the facet validity of the questionnaire can be tested; on the other hand, the common factors of the observed variables can be clustered to achieve the purpose of compressing variables [26][27][28][29]. e factor analysis method first needs to determine the questionnaire items for the KMO test and Bartlett sphere test.…”
Section: Results Analysismentioning
confidence: 99%
“…Factor analysis is a common analytical method to test the validity of the facet. rough exploratory factor analysis, on the one hand, the facet validity of the questionnaire can be tested; on the other hand, the common factors of the observed variables can be clustered to achieve the purpose of compressing variables [26][27][28][29]. e factor analysis method first needs to determine the questionnaire items for the KMO test and Bartlett sphere test.…”
Section: Results Analysismentioning
confidence: 99%
“…Using Naive Bayes method to model user consumption behaviour, our definition of user consumption behaviour is to establish hypothesis. e browsing behaviour on the e-commerce platform is generated because users have consumer demand and the final purchase of users depends on whether users browse the goods that meet the consumer demand or not [27][28][29][30]. erefore, we can model the user's consumption behaviour from the satisfaction degree of the characteristics of each product to the user's consumption demand.…”
Section: Parameter Estimation Of Naive Bayes Methodmentioning
confidence: 99%
“…Tarkas et al's experimental study on the effect of anterior cruciate ligament severance on the stress of the posterior horn of the medial meniscus found that, after the anterior cruciate ligament was severed, the stress on the posterior horn of the medial meniscus increased by 160% to 470% on average. The corners are subject to excessive load and are easily damaged [ 7 , 8 ]. ANM found that when applying anteroposterior force to the normal knee joint, the cruciate ligament is tightened before the meniscus takes effect, and the meniscus is less involved in blocking, but after the anterior cruciate ligament is ruptured, the tibia moves forward, and the posterior angle of the medial meniscus is filled between the tibial plateau and the femoral condyle, which acts as a wedge shape and prevents the tibia from moving further forward [ 9 ].…”
Section: Introductionmentioning
confidence: 99%